Evaluation of a Task-Shifting Strategy Involving Peer Educators in HIV Care and Treatment Clinics in Lusaka, Zambia - Born, Lonny J. (J Public Health Africa, 2012)
Rapid expansion of antiretroviral therapy (ART) and a shortage of health care workers (HCWs) required the implementation of a peer educator (PE) model as part of a task-shifting strategy in Lusaka District clinics. The purpose of this study was to evaluate patient and staff perceptions regarding whether the PE program: a) relieved the workload on professional HCWs; and b) delivered services of acceptable quality. Qualitative and quantitative data were gathered from five primary care clinics delivering ART in Lusaka, Zambia. Closed surveys were conducted with 148 patients receiving ART, 29 PEs, and 53 HCWs. Data was imported into Microsoft Excel to calculate descriptive statistics. Six focus group discussions and eight key informant (KI) interviews were conducted, recorded, transcribed, and coded to extract relevant data. Survey results demonstrated that 50 of 53 (96.1%) HCWs agreed PEs reduced the amount of counseling duties required of HCWs. HCWs felt that PEs performed as well as HCWs in counseling patients (48 of 53; 90.6%) and that having PEs conduct counseling enabled clinical staff to see more patients (44 of 53; 83%). A majority of patients (141 of 148; 95.2%) agreed or strongly agreed that PEs were knowledgeable about ART, and 89 of 144 (61.8%) expressed a high level of confidence with PEs performing counseling and related tasks. Focus group and KI interviews supported these findings. PEs helped ease the work burden of HCWs and provided effective counseling, education talks, and adherence support to patients in HIV care. Consideration should be given to formalizing their role in the public health sector.